Hubungan Pengetahuan, Pendidikan dan Sumber Informasi dengan Pemberian Kolostrum Pada Bayi Baru Lahir di Wilayah Kerja Puskesmas Sayur Matinggi Tahun 2017: Relationship between Knowledge, Education and Information Sources with the Administration of Colostrum in Newborns in the Work Area of ??the Matinggi Vegetable Health Center in 2017 - Nelly Karlinah (Journal of Midwifery and Nursing, 2019)
The Chairperson of the Indonesian Midwives Association (IBI) Central Executive Board stated that the organization has standardized services in assisting childbirth, namely the implementation of early initiation and exclusive 6-month breastfeeding. Colostrum is the milk produced during the first few days after birth. Colostrum has so many benefits that breastfeeding in the first weeks has a very important meaning for the development of the next baby. According to research on giving colostrum that Krista did, BC. There are still many mothers who lack or know enough about the importance of giving colostrum to newborns. Insufficient knowledge and educational level factors that influence this information is not well conveyed. The purpose of this study was to determine whether there is a relationship between knowledge, education and information sources of mothers with the provision of colostrum. The design used in this study is analytical with the Cross Sectional approach. The number of samples is 41 people. Sampling is done by Total Sampling. This research was conducted in the Sayur Matinggi Health Center Working Area. Data analysis with Chi Square. The results of this study note that the majority of respondents in the age range of 20-35 years were 37 people (90.3%). Most IRTs are 38 people (92.8%), the education level of the respondents is mostly highly educated as many as 26 people (63.4%), most of the respondents' knowledge about giving colostrum is good as many as 28 people (68.3%), some large was directly informed by 28 people (68.3%), most of the respondents carried out 22 people with colostrum (53.7%) and there was a relationship of knowledge with giving colostrum to newborns (value p = 0,0001). It is recommended that health workers in the Work Area of ??the Sayur Matinggi Health Center should increase the provision of information or counseling to mothers about giving colostrum. Keywords: Knowledge, education, source of information, and administration of colostrum